Correlation between Prostate Needle Biopsy and Radical Prostatectomy Gleason Gradings of 111 Cases with Prostatic Adenocarcinoma - Tavangar, S M; Razi, Ali; Mashayekhi, Reza (Urology Journal, 2009)
Purpose: There are conflicting reports in the literature about correlation of biopsy and prostatectomy Gleason scores in prostate carcinoma. The goal of this study was to determine the correlation of grading in these two types of pathologic materials. Materials and methods: The coupled Hematoxylin and Eosin slides of 111 patients with prostate carcinoma were collected. Gleason scores were determined. Patients who had undergone any therapy except surgery were excluded from the study. Correlation between grades was calculated by determination of correlation coefficient. Accuracy of biopsy grading in prediction of final grade was also determined by measuring the sensitivity, specificity, and positive and negative predictive values. Results: In 50 cases (45%), grade was underestimated in the biopsy. After dividing the cases into Gleason scores of 2 to 4, 5 to 6, 7, and 8 to 10, the most of undergraded cases (84.2%) were in the first group (Gleason score 2 to 4) and this rate reached 5% in the fourth group (Gleason score 8 to 10). The correlation coefficient measured was 0.535 in grade to grade comparing and 0.514 in group to group comparison of the specimens. In low-grade tumors, grading in biopsy, in spite of high sensitivity (90.9%), had low positive predictive value (26.3%). Conclusion: There is a moderate direct linear relationship between scores in biopsy and prostatectomy specimens. But there is a high probability of underestimation of real Gleason score of the radical prostatectomy specimen in low-grade tumors. Pathologists and urologists must consider the phenomenon of undergrading in reporting prostate specimens and managing patients.